1999
DOI: 10.21273/jashs.124.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Iris germanica Mediated by Agrobacterium tumefaciens

Abstract: A protocol was developed for production of transgenic iris plants (Iris germanica L. `Skating Party') from regenerable suspension cultures via Agrobacterium-mediated transformation. We tested a series of selection agents, and identified hygromycin and geneticin as the most suitable for selecting transformed iris cells. Suspension cultures of iris were cocultured for 3 days with A. tumefaciens LBA 4404(pTOK233) carrying an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This promoter was found to be the best for transformation of Iris germanica. This outcome further confirmed that Agrobacteriummediated transformation using CaMV35S can be applied to other important monocotyledonous ornamentals (Jeknic et al, 1999).…”
Section: Type Of Promoter Fused To the Coding Regionsupporting
confidence: 72%
See 1 more Smart Citation
“…This promoter was found to be the best for transformation of Iris germanica. This outcome further confirmed that Agrobacteriummediated transformation using CaMV35S can be applied to other important monocotyledonous ornamentals (Jeknic et al, 1999).…”
Section: Type Of Promoter Fused To the Coding Regionsupporting
confidence: 72%
“…In Iris germanica, LBA4404 gave remarkably higher transformation rates than EHA105 (Jeknic et al, 1999). In Agapanthus praecox, the same LBA4404 was found to be more effective than EHA101 (Suzuki et al, 2001).…”
Section: Agrobacterium Tumefaciens Strainsmentioning
confidence: 86%
“…Hygromycin and geneticin were found to be the best markers for selecting transformed cells. Over 300 morphologically normal transgenic plants carrying the GUS reporter gene were regenerated and stable transgene integration was confirmed by Southern hybridisation (Jeknic et al 1999).…”
Section: Irismentioning
confidence: 99%
“…Recently, particle bombardment and Agrobacteriummediated transformation have become the most popular and powerful approaches employed for the creation of horticulturally valuable characteristics such as novel flower colors, leaf shapes, dwarf forms, prolonged cut-flower vase-life, resistance to abiotic or biotic stresses such as viruses/ viroids, pathogens and insects (Teixeira da Silva et al, 2013). Up to date, genetic transformation in genus Iris has been reported only for I. germanica, where stable overexpression of the Lilium lancifolium capsanthin-capsorubin synthase (Llccs) gene in callus tissue resulted in color change from yellow to red-orange (Jeknić et al, 1999(Jeknić et al, , 2012. Genetic transformation of I. sibirica can also be an attractive way to create novel flower colors or to increase capacity for secondary metabolite production or content of essential oils.…”
Section: Introductionmentioning
confidence: 99%